2020
DOI: 10.1177/1947603520958146
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Two-Year Outcome of Cartilage Repair Surgery by Perichondrium Transplantation

Abstract: Objective The main purpose of the present study was to assess the risk for major revision surgery after perichondrium transplantation (PT) at a minimum of 22 years postoperatively and to evaluate the influence of patient characteristics. Design Primary outcome was treatment success or failure. Failure of PT was defined as revision surgery in which the transplant was removed, such as (unicondylar) knee arthroplasty or patellectomy. The functioning of nonfailed patients was evaluated using the International Knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Perichondrium transplantation patients were notified of plans to perform 7T MRI scanning of the transplants for research purposes at the time of participation in the long-term follow-up study of PT. 8 An information letter to explain the study was sent to eligible patients. A week thereafter, the patients were contacted by phone by the research physician (M.J.) to answer questions if any and to ask whether they were willing to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perichondrium transplantation patients were notified of plans to perform 7T MRI scanning of the transplants for research purposes at the time of participation in the long-term follow-up study of PT. 8 An information letter to explain the study was sent to eligible patients. A week thereafter, the patients were contacted by phone by the research physician (M.J.) to answer questions if any and to ask whether they were willing to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…5,7 Long-term results of PT were described by Janssen et al, who found that patient characteristics (i.e., time of symptoms prior to surgery, previous surgery in the index knee, and patient age) influence the outcome of PT at a follow-up of 22 years. 8 The previous results of ACT were described by Peterson et al, who found that after 10 to 20 years of follow-up, 92% of the patients were satisfied and would have the surgery again. 9 Intralesional osteophytes occurred frequently after both PT and ACT.…”
Section: Introductionmentioning
confidence: 92%
“…We would like to thank the authors for their response to our article. 1 Our main objective was to report the risk for major revision surgery after a long-term follow-up of perichondrium transplantation and to evaluate the influence of patient characteristics. As such, major revision surgery was defined as failure.…”
mentioning
confidence: 99%
“… Authors’ Note The authors’ declarations of personal and financial interests are unchanged from those in the original article. 1 …”
mentioning
confidence: 99%
“…We read with interest the article of Janssen and colleagues regarding the evaluation of perichondrium transplantation in patients affected by articular cartilage defects of the knee. 1 The authors provided the failure rate of this cartilage procedure at a minimum of 22 years of follow-up, and the clinical outcome of the non-failed patients was evaluated using patient-reported outcome measurements (PROMs). They described an overall 66% survival of patients still without a major revision surgery (graft removal or arthroplasty) and they also underlined the influence of some factors such as age, previous symptoms duration, and previous surgery on the final outcome.…”
mentioning
confidence: 99%